The IRIS Global Seismographic Network - R. Butler (Annals of Geophysics, 1994)
Since the last FDSN meeting in December 1992, the IRIS Global Seismographic Network (GSN) has made significant progress toward meeting its goals of a uniform, globally distributed, network of broadband seismographic stations. More GSN stations were installed or upgraded than in any previous year. A total of 15 new stations entered into operation, bringing the total number of stations in the GSN to 54. Additionally, 4 existing GSN stations were upgraded with 24-bit data acquisition systems.